Analysis of Car-to-Car Beaconing with Network Coding - Ali, Nasir; Baselt, Daniel; de Meer, Hermann (Electronic Communications of the EASST, 2011)
Lack of updated information due to a high beacon loss rate is a key challengein car-to-car beaconing strategies. One potential solution for this issue is tore-broadcast lost beacons. However, the repeated dissemination of each lost beaconis infeasible due to the limited bandwidth of wireless channels. To overcome thislimitation, network coding is a promising technique, through which a node combines(i.e. codes) multiple packets from different sources and re-broadcasts themthrough one transmission for the efficient bandwidth usage. In the past, networkcoding has been employed only for data packets. In this paper, this idea is used forperiodic beacons in car-to-car communication to analyze, how much it is effectivefor the recovery of lost beacons. To this end, we propose two approaches: randomselection and radius-based, and compare them to determine, which scheme recoversmore beacons. We evaluate these approaches in both sparse and dense highwaytraffic scenarios with probabilistic radio propagation characteristics.